High-Fidelity, Weak-Light Polarization Gate Using Room-Temperature Atomic Vapor. (18th March 2015) - Deng, L; Hagley, E W; Li, Runbing; Zhu, Chengjie
Abstract: Using a polarization-selective-Kerr-phase-shift technique we demonstrate a fast, all-optical, high-fidelity polarization gate in a room-temperature atomic medium. By writing a π- phase shift to one selected circularly-polarized component of a linearly-polarized input signal field and by equalizing the gain of both circularly-polarized components we can maintain the original strength of the signal field and yet achieve a perfect 90° rotation of its linear polarization, demonstrating a fast, high-fidelity, dynamically-controlled polarization gate operation. The orthogonal linear polarization switching field intensity can be as low as 2 mW/cm 2 using a warm rubidium vapor, which is equivalent to a 100-nanosecond pulse containing about 200 photons and confined in a typical commercial photonic hollow-core fiber with a 5-μm mode diameter.